Effect of fish feed containing two Chinese herbal extracts (Ganodema Iucidum and Lonicera japonica) on the non-specific immune system of Nile tilapia, Oreochromis niloticus (preliminary results) - Ardó, László; Guojun, Yin; Jeney, Zsigmond; Pao, Xu; Jeney, Galina (Acta Agraria Debreceniensis, 2007)
The effect of two Chinese herbs (Ganoderma lucidum and Lonicera japonica) on non-specific immune response of tilapia was examined. In addition to the control (no herbs), three diet variations were used. These contained 1.0% of Lonicera, 1.0% of Ganoderma and a mixture of Ganoderma (0.5%) and Lonicera (0.5%). The respiratory burst and phagocytic activity of blood leukocytes were monitored. Three weeks after feeding, the fish were infected with Aeromonas hydrophila. The results of this study showed that feeding tilapia with Ganoderma and Lonicera alone or in combination enhanced the phagocytosis of blood leukocytes, but not the respiratory burst activity. Both herbs, when used alone or in combination, reduced mortality after challenge with A. hydrophila. The highest mortality was observed in the control fish – 56.66%, and fish fed with Lonicera extract – 43.33% while 30% of fish died in the group fed with Ganoderma and the lowest mortality (20%) was observed when the fish were fed with a combination of the two herbs. It can be concluded that the herb extracts added to this diet act as immuno-stimulants and appear to improve the immune response and disease resistance of tilapia.